(3GdTaG HJYQja Mbhb GdoeUWaj (B((3Udi Gddg Ydjg hSde(B)s - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3CMeO Hf Ydj Hf eMeO GdMfaj s)
(3ChdgG (B:s
(3bGd Gdabjg YjGV Hf ehSi GdMeO ddg GdeJaQO HGSeg GdCSei GdoeNJU HGdedc GdCYR GdMei s
(3BNQgG (B:s
(3hUdhGJg Ydi SjOfG hfHjfG eMeO NGJe GdfHjjf hYdi Bdg hUMHg CLejf hSde JSdjekG cKjQkGJe cJGH GdTaG HJYQja Mbhb GdoeUWai s
(3fSNI SGOSIs
(3NRGFfjI fajSIs
(3hHBNQgG ebGHdI hSeGY eDQN SfI (B850(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs